Pelatihan dan Penguatan Kemampuan Guru-Guru Mata Pelajaran Seni Budaya di Lingkungan Dinas Pendidikan Kab. Kutai Timur - Jamil, Jamil; Alamsyah, Alamsyah; Muhlis, Muhlis (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LP2M), Universitas Mulawarman, 2025)
Abstract Many of the teachers of Art and Culture subjects do not have scientific knowledge and some of them are not graduates from Bachelor of Arts and Culture. Likewise, it is necessary to develop themselves by continuing to improve knowledge to strengthen their literacy skills. To develop and improve their abilities in these subjects, the East Kutai Regency Education Agency conducted training to improve the skills of the teachers with materials presented by professional trainers based on their respective fields of knowledge consisting of teachers and arts and culture practitioners. This program received a positive response from the participants by attending the training enthusiastically and it is hoped that this training improve their abilities to be transmitted to students in order to have broad knowledge and understanding of arts and culture learning including: the use of technology in art learning, increasing creativity and innovation, understanding local wisdom and traditional arts where Indonesia is the country with the most ethnic groups that have different arts and cultures.